Static strength of axially loaded tubular KT-joints at elevated temperatures: Study of geometrical effects and parametric formulation. (September 2018) - Azari Dodaran, Neda; Ahmadi, Hamid; Lotfollahi-Yaghin, Mohammad Ali
Abstract: This paper aims to study the structural behavior of tubular KT-joints subjected to axial loading at fire induced elevated temperatures. At first, a finite element (FE) model was developed and validated against the data available from experimental tests. Then, a set of 810 FE analyses were performed to study the influence of temperature and dimensionless geometrical parameters ( β, γ, θ, and τ ) on the ultimate strength and initial stiffness. The joints were analyzed under two types of axial loading and five different temperatures (20 °C, 200 °C, 400 °C, 550 °C, and 700 °C). Up to now, there has not been any design formula available for determining the ultimate strength of KT-joints at elevated temperatures. Hence, after parametric study, a new equation was developed through nonlinear regression analyses, for calculating the ultimate strength of KT-joints subjected to axial loading at elevated temperatures. Highlights: The ultimate strength and failure modes of tubular KT-joints at fire-induced elevated temperatures were investigated. Tubular KT-joints were subjected to two types of axial loading. Results of 810 steady-state FE analyses were used for the parametric study. A set of new design equations was derived to calculate the ultimate strength of KT-joints subjected to axial loading.